2020
DOI: 10.3389/fimmu.2020.00348
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulators of T Helper 17 Cell Differentiation in Health and Autoimmune Diseases

Abstract: T helper (Th) 17 cells are a subtype of CD4 T lymphocytes characterized by the expression of retinoic acid-receptor (RAR)-related orphan receptor (ROR)γt transcription factor, encoded by gene Rorc. These cells are implicated in the pathology of autoimmune inflammatory disorders as well as in the clearance of extracellular infections. The main function of Th17 cells is the production of cytokine called interleukin (IL)-17A. This review highlights recent advances in mechanisms regulating transcription of IL-17A.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
102
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(107 citation statements)
references
References 103 publications
0
102
0
Order By: Relevance
“…44 CXCLs then attract myeloid cells such as neutrophils to infected or injured tissues. 44 In contrast, Treg cells express anti-inflammatory cytokines (IL-4, IL-10, and TGF-β) and control excessive immune responses. 45,46 The Treg/Th17 balance plays an important role in the severity of lung injury 47 and in uncontrolled systemic inflammation characterizing acute lung injury (ALI)/ ARDS ( Figure 1C).…”
Section: Role Of Treg/ Th17 Cell R Ati O In Covid -19 Pathog Ene S Ismentioning
confidence: 99%
See 1 more Smart Citation
“…44 CXCLs then attract myeloid cells such as neutrophils to infected or injured tissues. 44 In contrast, Treg cells express anti-inflammatory cytokines (IL-4, IL-10, and TGF-β) and control excessive immune responses. 45,46 The Treg/Th17 balance plays an important role in the severity of lung injury 47 and in uncontrolled systemic inflammation characterizing acute lung injury (ALI)/ ARDS ( Figure 1C).…”
Section: Role Of Treg/ Th17 Cell R Ati O In Covid -19 Pathog Ene S Ismentioning
confidence: 99%
“…These two CD4 + T‐cell subsets have different actions 43 . Th17 cells are mainly characterized by their production of inflammatory cytokines such as IL‐17A, 42 which activates target cells and induces chemokine (C–X–C motif) ligands (CXCLs) 44 . CXCLs then attract myeloid cells such as neutrophils to infected or injured tissues 44 .…”
Section: Role Of Treg/th17 Cell Ratio In Covid‐19 Pathogenesismentioning
confidence: 99%
“…Further analysis found that RORC and S100A12 were associated with psoriasis severity. The nuclear receptor retinoic acid receptor-related orphan receptor gamma (murine form "RORγ" or human form "RORC") was a key transcription factor for the production of IL-17 and involved in in ammatory response of psoriasis [20] . Compared with severe psoriasis, mild psoriasis was characterized by higher IL-17A expression in psoriatic lesion [21] , which is consistent with the alteration of RORC in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Th17s are a subtype of CD4-positive T cells specialized for mounting immune responses against fungi and some extracellular bacteria. In addition to IL-17A, Th17s produce IL-17F, IL-21, IL-22, and IL-26 (79). Because IL-17 is a potent proinflammatory cytokine that amplifies ongoing inflammation, aberrant regulation of Th17s contributes to development of inflammatory and autoimmune disorders.…”
Section: The Importance Of Gut Microbiota In Human Healthmentioning
confidence: 99%